(untitled) (Journal of Parents and Teachers, 2013)
We are currently living in a time of crisis where "zombie ideas" prevail, which are those that have been shown to not work but to resist dying. Likewise, in this issue of Parents and Teachers, reflections on the transformation of education due to the integration of digital resources are presented.